Prosocial Education: An Intercultural Perspective and School Coexistence in Ecuadorian Adolescents - Rivera, Sara Nila Yagual; Alvarado, Edgar Fabián Cobos; Vélez, Wilson Alexander Zambrano (Journal of Posthumanism, 2025)
Prosocial education is inevitably the path to improved educational quality in contemporary educational systems, and specifically at the basic levels of continuing education. In Ecuador, basic educational institutions still struggle to establish links between these essential categories in the teaching-learning process. The objective of this study is to characterize the correlation between interculturality and school coexistence in a group of adolescents in their first and second years of higher basic education at the Juan Jacob Rosseau and Juan Dagoberto Montenegro centers in the province of Santa Elena, Ecuador. A quantitative study was conducted with a relational cross-sectional design. The sample size was determined probabilistically through stratified random sampling by sections of the two educational institutions, with a confidence level of 95%. The sample consisted of 72 students, aged 11-15 years, with an M=13 and SD=0.98. The main results show the strongest correlations between: Diversity ↔ Attitudes (r=0.86), Communication ↔ Conflicts (r=0.85), and Attitudes ↔ Communication (r=0.84). The Nature of Help subscale shows the lowest correlations (r≈0.67–0.70) with the interculturality subscales (Diversity, Attitudes, Communication). In conclusion, the subscales Motivation, Nature of Help, Context, Impact and Outcome, Cultural Contact and Diversity, Attitudes and Perceptions, Communication and Adaptation, and Conflict and Resolution all had positive correlations with each other, revealing a positive relationship between prosocial behavior, interculturality, and school coexistence in these adolescents surveyed.